An Investigation of the Reactions between Azido Alcohols and Phosphoramidites - Wu, Jian; Bishop, Lee; Guo, Jiatong; Guo, Zhongwu (Synlett, 2019)
The reactions of several β-, γ-, and δ-azido alcohols with dibenzyl and dimethyl N,N-diisopropylphosphoramidites were examined. Detailed analysis of the intermediates and products formed from the reactions under different conditions provided useful information to gain insights into their mechanisms involving intramolecular Staudinger reaction, as well as the structure–reactivity relationships of both substrates. The reactions of γ- and δ-azido alcohols with dibenzyl N,N-diisopropylphosphoramidite could produce 6- and 7-membered cyclic phosphoramidates, thereby providing a new synthetic method for these biologically important molecules.
Keywords: Staudinger reaction; azido alcohol; phosphoramidite; cyclic phosphoramidate; cyclization